Prophets of God or Neo-Diviners? A Theological Assessment of Prophecy in Zambia Today - Banda, Devison T. (Prophecy Today: Reflections from a South Africa Context, 2016)
In Prophecy today: reflections from a Southern African context, a group of theologians and scholars of religion from Zambia and South Africa reflects upon these questions. Anthropologists, Biblical scholars, practical theologians and others shine their light on what prophecy can mean today in this context. This book aims at stimulating a continuing Southern African discourse on this very interesting and relevant aspect of Christianity in our region. The book consists of 15 different articles by well-known scholars and has been ably compiled and edited by Dr Hermen Kroesbergen, lecturer in Systematic Theology and Philosophy of Religion at Justo Mwale University, Lusaka, Zambia.
Keywords: Religion; Theology & Religion